Can stakeholder theory add to our understanding of Malaysian environmental reporting attitudes? / Evangeline Elijido-Ten - Elijido-Ten, Evangeline (Accounting Research Institute (ARI) & Faculty of Accountancy, 2009)
This research aims to ascertain whether stakeholder theory could, in fact, add to our understanding of the corporate environmental disclosure attitudes from a developing country perspective. Multiple ordinary least squares regression was used where Ullmann's (1985) three dimensional stakeholder model was operationalized to test whether the quality and quantity of annual report environmental disclosures (AREDs) were associated with the proxies for stakeholder power, strategic posture and economic performance. Of the three stakeholders represented, only government power (GP) was significant; the other two - shareholder power (SP) and creditor power (CP) - were not significantly related to AREDs. The results also showed that proxies for strategic posture were significant and positively related to AREDs while the economic performance proxy was not. Subsequent interviews with CEOs of disclosing firms confirmed that while AREDs were used to disseminate environmental information to stakeholders, there was not much demand from both shareholders and creditors given the low level of environmental awareness in Malaysia.